Effect of Campylobacter fetus on in vitro fertilization and embryonic development of preimplantation bovine embryos - Cagnoli, Claudia Inés; Chiapparrone, María Laura; Cacciato, Claudio Santiago; Rodríguez, Marcelo Gastón; Catena, María del Carmen; Aller Atucha, Juan Florencio (Elsevier, 2024)
Campylobacter fetus is an important veterinary pathogen that causes campylobacteriosis. This disease causes decreased productivity of cattle by inducing reproductive losses. Although several virulence factors have been recognized in C. fetus, including a cytolethal distending toxin (CDT), the exact mechanism responsible for embryonic death remains unknown. The aim of this work was to evaluate the effect of C. fetus subsp. fetus (Cff) and C. fetus subsp. venerealis (Cfv), and their toxin activity on the in vitro fertilization of bovine ova and early embryonic development. Two different experiments were performed. In Experiment 1, a total of 1524 cumulus–oocyte complexes (COCs) were inseminated, distributed into three groups: two of them infected with the microorganism (Cff, Cfv) and a control group. Percentages COCs cleaved were similar among groups (p = 0.1243); however, the embryonic development rate (blastocyst at day 7) in the control group was greater (p < 0.001) than those obtained in Cff and Cfv groups. In experiment 2, a total of 746 COCs were inseminated, divided into three groups: two of them treated with the bacterial-free culture filtrates to test toxin activity (Cff-CDT, Cfv-CDT) and a control group. Both cleavage and embryonic development rates were greater (p < 0.001) in the control group than those obtained in Cff-CDT and Cfv-CDT groups. This study provides evidence that both subspecies of C. fetus do not interfere with fertilization but do affect in vitro embryonic development. It is the first report on the biological effect of the CDT on bovine embryonic development.